Tree-rings analysis to reconstruct atmospheric mercury contamination at a historical mining site - Baroni, Davide; Ancora, Stefania; Franzaring, Jürgen; Loppi, Stefano; Monaci, Fabrizio (Frontiers in Plant Science, 2023)
Mercury (Hg) is a global environmental concern due to its toxicity (especially high in methylated form) and the long-range distribution of its gaseous elemental form (GEM). Hg-contaminated areas, such as abandoned mining sites, pose intrinsic difficulties for their management and heavy monitoring costs. In these environments, plant-based solutions may play a key role in the ecosystem quality assessment and support remediation strategies, combining reliability and cost-effectiveness. In this study, we adopted a biomonitoring approach by using tree rings of four different species collected in the proximity of the mining-metallurgical area of Abbadia San Salvatore, central Italy, a major former Hg mining district whose reclamation is currently in progress. Our dendrochemical analysis was aimed at identifying the historical changes of local atmospheric Hg contamination and at singling out, for the first time in the study area, other potentially toxic elements (PTEs) associated with the past mining activity. Collected cores dated back to early as 1940 and provided the temporal patterns of atmospheric Hg emission vs the produced liquid quantities, so reconstructing the historical impact of the mining site on nearby terrestrial ecosystems and resident human population. Current GEM contamination was found about twenty times lower than that of the fully operational mine periods. From a first survey on other PTEs, thallium (Tl) and lead (Pb) appeared to be potentially associated with the mining activity, thus suggesting new working assumptions for further dendrochemical analyses and for the inclusion of Pb in human biomonitoring surveys of the Mt. Amiata area, actually not present in the control list. The results prompt a more thorough assessment by tracking for a longer time span a critical site that is an ideal open-field lab to study the ecophysiology of different tree species in relation to other environmental behavior of PTEs for betterassessing wildlife and human exposures.